Servants of Allah : African Muslims enslaved in the Americas - Diouf, Sylviane A. (Sylviane Anna), 1952- (New York University Press, 2013)
It is widely assumed that the faith enslaved West African Muslims brought to the Americas was quickly absorbed into their new Christian milieu. Yet, as the author demonstrates in this book, Islam flourished during slavery on a large scale. Even while enslaved, many Muslims managed to follow most of the precepts of their religion. Often literate, urban, and well-traveled, they drew on their organization, solidarity, and the strength of their beliefs to play a major part in the most well-known slave uprisings. But for all their accomplishments and contributions to the history and cultures of the African diaspora, the Muslims have been largely ignored. This book illuminates the role of Islam both in the lives of individual practitioners and in communities. It shows that though the religion did not survive in its orthodox form, its mark can be found in certain religions, traditions, and artistic creations of people of African descent. This fifteenth-anniversary edition has been updated to include new materials and analysis, a review of developments in the field, prospects for new research, and illustrations. -- Description from back cover.